Environmental concentrations of 2, 4-DTBP cause immunotoxicity in zebrafish (Danio rerio) and may elicit ecological risk to wildlife. (December 2022) - Liu, Wang; Zhang, Jiye; Liang, Xuefang; Wang, Yuchen; Liu, Ruimin; Zhang, Ruiqing; Zha, Jinmiao; Martyniuk, Christopher J.
Abstract: Synthetic phenolic antioxidant 2, 4-di- tert -butylphenol (2, 4-DTBP) has gained growing concerns due to relatively high concentrations in aquatic ecosystems. There are, however, significant knowledge gaps regarding its potential toxicity to aquatic organisms. In this study, zebrafish ( Danio rerio ) larvae were exposed to 0.01, 0.1, or 1 μM 2, 4-DTBP for 6 d. Transcriptomic analysis of larvae revealed that biological processes related to anti-inflammatory function of macrophage M2 lineage were inhibited by 0.01 μM 2, 4-DTBP. Decreases of transcripts related to the IL1B-MYD88-NF-κB pathway (i.e., il1b, il1rl1, myd88, irak4, irak1, traf6, ikbkg, nfkbia, nfkb ) and protein levels of NF-κB in larvae intestine confirmed anti-inflammatory effects of 2, 4-DTBP. Subsequently, larvae exposed to 2, 4-DTBP were challenged with E. coli and showed higher survival rate, suggesting sustained activation of inflammation via LPS can be attenuated by 2, 4-DTBP. Moreover, histological examination revealed that intestine barrier was compromised and there was an imbalance of intestine macrophage homeostasis. Food intake was also reduced following exposure to 0.1 and 1 μM 2, 4-DTBP. In addition, a risk assessment revealed that 2, 4-DTBP in surface water pose low to high ecological risks to aquatic organisms. Taken together, exposure to environmentally relevant concentrations of 2, 4-DTBP could negatively affect immune response in zebrafish and may elicit ecological risk in fish population. Graphical abstract: Image 1 Highlights: 2, 4-DTBP affects immunomodulation and the intestine barrier in zebrafish. 2, 4-DTBP exhibits anti-inflammatory properties via NF-κB pathway inhibition. Exposure to 2, 4-DTBP reduced feeding capacity in larvae. 2, 4-DTBP exerts moderate or high risk to fish.